On Computational Modelling of Strain-Hardening Material Dynamics (Communications in Computational Physics, 2012)
In this paper we show that entropy can be used within a functional forthe stress relaxation time of solid materials to parametrise finite viscoplastic strain-hardening deformations. Through doing so the classical empirical recovery of a suitable irreversible scalar measure of work-hardening from the three-dimensional stateparameters is avoided. The success of the proposed approach centres on determination of a rate-independent relation between plastic strain and entropy, which is foundto be suitably simplistic such to not add any significant complexity to the final model.The result is sufficiently general to be used in combination with existing constitutivemodels for inelastic deformations parametrised by one-dimensional plastic strain provided the constitutive models are thermodynamically consistent. Here a model for thetangential stress relaxation time based upon established dislocation mechanics theoryis calibrated for OFHC copper and subsequently integrated within a two-dimensionalmoving-mesh scheme. We address some of the numerical challenges that are faced inorder to ensure successful implementation of the proposed model within a hydrocode.The approach is demonstrated through simulations of flyer-plate and cylinder impacts.